Financing Risk Management Based on Profit Sharing Sharia Rural Bank (Sudy on BPRS HIK Parahyangan) - Istutik, Istutik; Tuakia, Hedher (Assyarikah: Journal of Islamic Economic Business, 2024)
The banking industry in its operations is full of risks that can disrupt the survival of banks, including Sharia Rural Bank (BPRS). The characteristics of BPRS products and services require identification, measurement, monitoring and risk control functions that are in accordance with sharia banking business activities. The composition of profit sharing based financing at BPRS is only 14%, the level of profitability with ROA and ROE starting in 2014 has decreased. On the other hand, the non-performing financing (NPF) ratio continues to increase. Meanwhile, the opportunity to increase profit sharing-based financing is very high because the number of MSMEs is very large.The number of BPRS in Indonesia until 2023 is 173, of which there are 80 BPRS in the island of Java. Secondary data collection is carried out through annual reports. BPRS HIK Parahyangan was chosen as the research object. Analysis of the implementation of risk management follows the stages of the risk management process. BPRS HIK Parahyangan's understanding of risk management and its implementation.The research results show the fact that in the year period studied, namely 2020-2022, BPRS HIK Parahyangan has implemented risk management and risk mitigation well. The risk management process is understood and implemented by BPRS HIK Parahyangan, always applying the principle of prudence in providing financing and focusing on clients who have a proven track record. So that BPRS HIK Parahyangan can maintain healthy financing quality with a controlled problem financing ratio.